2009
DOI: 10.4141/cjps07072
|View full text |Cite
|
Sign up to set email alerts
|

The physiological genetic effects of 1BL/1RS translocated chromosome in "stay green" wheat cultivar CN17

Abstract: . 2009. The physiological genetic effects of 1BL/ 1RS translocated chromosome in ''stay green'' wheat cultivar CN17. Can. J. Plant Sci. 89: 1Á10. Rye (Secale cereale L.) chromosome arm 1RS in the wheat (Triticum aestivum L.) genetic background has potential significance for yield improvement without affecting its resistance to several diseases. A new wheat cultivar, Chuannong17 (CN17), carrying the wheat-rye 1BL/1RS translocated chromosome, exhibited ''stay green'' phenotypes. To determine the genetic behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Such findings have been reported in durum and wheat (Rampino et al 2006;Luo et al , 2009. Two wheat cultivars, CN12 and CN18, with the wheat-rye 1BL/ 1RS translocation (Tang et al 2008) that were released into southwest China in 2003 exhibit a similar stay-green phenotype to that of CN17 (Luo et al 2009), the sister line of both CN12 and CN18 (Luo et al 2008;Tang et al 2008).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Such findings have been reported in durum and wheat (Rampino et al 2006;Luo et al , 2009. Two wheat cultivars, CN12 and CN18, with the wheat-rye 1BL/ 1RS translocation (Tang et al 2008) that were released into southwest China in 2003 exhibit a similar stay-green phenotype to that of CN17 (Luo et al 2009), the sister line of both CN12 and CN18 (Luo et al 2008;Tang et al 2008).…”
Section: Introductionmentioning
confidence: 66%
“…Wheat (Triticum aestivum L.) is one of the most important crops, and its yield potential has significantly improved, increasing above the global biomass (Reynolds et al 2000). However, the maintenance of longer photosynthetic competence is one of the most effective ways to increase wheat biomass yield and yield potential Luo et al , 2009, especially after flowering in the flag leaf, from which most accumulated wheat assimilates in grains mainly come (Austin et al 1977;Sylvester-Bradley et al 1990). Therefore, improving the photosynthetic competence of the flag leaf could play a potentially significant role in increasing wheat yield.…”
Section: Introductionmentioning
confidence: 96%
“…However, increases in radiation use efficiency obtained by genetic manipulation of the senescence programme should be accompanied by other adaptations in the whole-plant physiology. Stay-green phenotypes that have a sustained long period of high photosynthetic capacity could increase grain numbers per area as well as result in a greater number of stronger sinks that would again enhance photosynthetic rates (Luo et al 2009). Some staygreen wheat cultivars have larger grains (Chen et al 2010).…”
Section: Relationship Between Photosynthetic Duration and Biomass Yieldmentioning
confidence: 99%
“…Three wheat cultivars, CN12, CN17, and CN18, were developed from the progenies of a wheatrye wide cross and are sister lines with a wheat-rye 1BL/1RS translocation (Tang et al 2008). Many regions in southwest China grow these cultivars because of their high yield (Luo et al 2009) and good resistance to diseases, including stripe rust (Luo et al 2008) and powdery mildew ). Previous studies have demonstrated that CN12, CN17, and CN18 are functional stay-green varieties that maintain high photosynthetic competence during the grain-filling stage (Luo et al 2006) and are associated with a high yield (Luo et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many regions in southwest China grow these cultivars because of their high yield (Luo et al 2009) and good resistance to diseases, including stripe rust (Luo et al 2008) and powdery mildew ). Previous studies have demonstrated that CN12, CN17, and CN18 are functional stay-green varieties that maintain high photosynthetic competence during the grain-filling stage (Luo et al 2006) and are associated with a high yield (Luo et al 2009). A complete understanding of the underlying molecular mechanism and genetic basis, particularly which genes or chromosome regions are crucial in controlling these traits, is notably important for further use of the varieties in wheat yield improvement.…”
Section: Introductionmentioning
confidence: 99%